First occurrence of Calvatia cyathiformis (Basidiomycota) in caatinga, Pernambuco State, Brazil - Wartchow, Felipe; Silva, Sônia M. da (SITIENTIBUS série Ciências Biológicas, 2007)
Calvatia cyathiformis (Bosc) Morgan is found for the first time in caatinga. Description, discussion and photography of basidiomata are given.